Synchrotron‐radiation‐based X‐ray micro‐computed tomography reveals dental bur debris under dental composite restorations. (1st April 2016) - Hedayat, Assem; Nagy, Nicole; Packota, Garnet; Monteith, Judy; Allen, Darcy; Wysokinski, Tomasz; Zhu, Ning
Abstract : Synchrotron‐radiation‐based micro‐computed tomography was used to study dental bur debris of metallic nature under a composite restorative dental filling material. The debris is made of tungsten carbide–cobalt, which is bio‐incompatible. Abstract : Dental burs are used extensively in dentistry to mechanically prepare tooth structures for restorations (fillings), yet little has been reported on the bur debris left behind in the teeth, and whether it poses potential health risks to patients. Here it is aimed to image dental bur debris under dental fillings, and allude to the potential health hazards that can be caused by this debris when left in direct contact with the biological surroundings, specifically when the debris is made of a non‐biocompatible material. Non‐destructive micro‐computed tomography using the BioMedical Imaging & Therapy facility 05ID‐2 beamline at the Canadian Light Source was pursued at 50 keV and at a pixel size of 4 µm to image dental bur fragments under a composite resin dental filling. The bur's cutting edges that produced the fragment were also chemically analyzed. The technique revealed dental bur fragments of different sizes in different locations on the floor of the prepared surface of the teeth and under the filling, which places them in direct contact with the dentinal tubules and the dentinal fluid circulating within them. Dispersive X‐ray spectroscopy elemental analysis of the dental bur edges revealed that the fragments are made of tungsten carbide–cobalt, which is bio‐incompatible.